2008
DOI: 10.1159/000177016
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Endoscopy Using the Double-Balloon Technique: Four-Year Results in a Tertiary Referral Hospital in Brazil

Abstract: Background: Double-balloon enteroscopy (DBE) allows evaluation and therapy for various small bowel diseases. In this series the outcome of a 4-year experience in a tertiary hospital school in Brazil is reported. Methods: A total of 457 consecutive DBE were performed in 418 patients from August 2004 to August 2008. 93 patients with several indications, whose aim was not the evaluation of suspected diseases of the small bowel mucosa, were excluded, therefore leaving 364 DBE in 325 patients for analysis. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In a Japanese cohort using DBE, complete enteroscopy was achieved in 86%. 15 Early Western series report total enteroscopy rates between 0% 13 and 42%, 16 and mostly less than 20%. 3,4,17 However, one recent study from Europe reported more favorable results, which may suggest a learning curve effect.…”
Section: Discussionmentioning
confidence: 99%
“…In a Japanese cohort using DBE, complete enteroscopy was achieved in 86%. 15 Early Western series report total enteroscopy rates between 0% 13 and 42%, 16 and mostly less than 20%. 3,4,17 However, one recent study from Europe reported more favorable results, which may suggest a learning curve effect.…”
Section: Discussionmentioning
confidence: 99%
“…To date, OGIB has been the most frequent clinical indication for DBE and accounts for 50–70% of all examinations performed 3,15–20,26,41,42 …”
Section: Clinical Indications and Resultsmentioning
confidence: 99%
“…With regard to DBE findings, vascular lesions are discovered more frequently in Western patients, 3,12–19 whereas inflammatory changes and/or tumors are found more frequently in Japanese patients 15,20–22 . Although there is no clear‐cut explanation for this phenomenon, differences in the age and selection of patients could play a role, as Eastern DBE patients are younger and Japanese patients more often undergo the procedure for abdominal pain/occlusion or suspected small bowel tumors 13,20–22 .…”
Section: Dbe: the ‘Japanese’ And The ‘Western’ Perspectivementioning
confidence: 99%
“…55 In our centre, no major complications have been reported for 364 DBE procedures, 112 of which included biopsy collection. 56…”
Section: Discussionmentioning
confidence: 99%
“…55 In our centre, no major complications have been reported for 364 DBE procedures, 112 of which included biopsy collection. 56 The amount of GI tissue obtained from the pre-and postoperative biopsies in this study was sufficient for gene expression analysis for all enrolled patients. However, the excluded stomach portion was inaccessible for postoperative biopsy sample collection in some patients because of stenosis in the biliopancreatic limb (n ¼ 3) and the difficulty of reaching this portion of the GI tract (n ¼ 10).…”
Section: Discussionmentioning
confidence: 99%